2011
DOI: 10.1093/humrep/der154
|View full text |Cite
|
Sign up to set email alerts
|

Use of metformin before and during assisted reproductive technology in non-obese young infertile women with polycystic ovary syndrome: a prospective, randomized, double-blind, multi-centre study

Abstract: ClinicalTrials.gov Identifier: NCT00159575.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 28 publications
6
68
0
1
Order By: Relevance
“…Among IVF-treated women, there was no difference in clinic pregnancy rate between metformin and placebo groups. However, due to spontaneous pregnancies that occurred prior to IVF, there was a significantly higher clinical pregnancy rate (50 % versus 33.3 %, p= 0.04) and live birth rate (48.6 % versus 32.0 %, p=0.04) in the metformin group [13]. Interestingly, in a previous doubleblind randomized control trial performed by the same group in which PCOS patients were stratified by weight, there were no differences between pregnancy and live birth rates in the metformin versus placebo groups among all patients.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Among IVF-treated women, there was no difference in clinic pregnancy rate between metformin and placebo groups. However, due to spontaneous pregnancies that occurred prior to IVF, there was a significantly higher clinical pregnancy rate (50 % versus 33.3 %, p= 0.04) and live birth rate (48.6 % versus 32.0 %, p=0.04) in the metformin group [13]. Interestingly, in a previous doubleblind randomized control trial performed by the same group in which PCOS patients were stratified by weight, there were no differences between pregnancy and live birth rates in the metformin versus placebo groups among all patients.…”
Section: Discussionmentioning
confidence: 95%
“…The two most common endpoints are a positive pregnancy test (35 %) and at 12 weeks gestational age (33 %). This trend in the variability of pretreatment (if any) and treatment duration seems to be mirrored by various major studies as well-ranging from≥16 weeks to the beginning of ovulation induction for the starting time of metformin, and from hCG administration to the 12th week of pregnancy for the stopping time [10][11][12][13][14][15][16][17][18][19]. However, analysis shows no significant effect on pregnancy and live birth rates among PCOS patients after these studies were categorized by long term pretreatment (>3 weeks), short term pretreatment (≤3 weeks), or no pretreatment, and by stopping time of metformin with hCG administration, oocyte retrieval and embryo transfer as endpoints [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Live births were noted in 48.6% of the women who received metformin, while among those who received placebo -32%. The researchers emphasized that the clinical outcome resulted from increasing the chance for spontaneous pregnancy in the group receiving metformin, and was not the effect of the improvement of the effectiveness of IVF [17]. It was also confirmed that the reduction of body weight in women with PCOS, leading to reduction in insulin resistance, increased the chance for regaining spontaneous ovulatory function or improvement of the response to the stimulation of the ovaries [18].…”
Section: Objectivementioning
confidence: 96%